LIBRARY MATERIAL COLLECTION AS ASPECT OF MAIN STRENGTH IN LIBRARY INFORMATION SERVICES : THE ROLE OF LIBRARIAN IN MAINTAINING LIBRARY MATERIAL COLLECTION I INDONESIAN LIBRARY - BAKHTIYAR (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2020)
The research aims to find out: (1). The maintenance of library collections. (2). The role of the librarian in maintaining library collections. The object of research relies on the content of the role of librarians in maintaining library collections. The scope of the study focuses on the realization of the role of librarians in excellent service by preserving the collection of library materials. Research using a historical approach is characterized by critical inquiry. The method of finding data is library research using qualitative descriptive analysis and content analysis and observation to support theoretical construction. The results of the study are; (1). The urgency of maintaining library material collections include; (a). The collection of library materials is primary in the library system (b). Procurement of literature requires expensive costs and sometimes even difficult to obtain. (C). The value of the information contained therein is very high and cannot be measured with material. (2). The role of librarians in maintaining library collections includes: (a). librarians play a role in mastering the management of library collection preservation that is capable of making effective planning and prevention. (b). Librarians play a role in having understanding, knowledge, expertise and skills in the management of the collection of library materials, so that they are able to play an active role in the prevention, mitigation of damage and loss caused by natural disasters, natural disasters and humans. (c). Librarians play an active role in controlling the safety factors, actions and methods in dealing with damage to library collections caused by natural, natural and human disasters